A Common Approach to Geo-Referencing Building Models in Industry Foundation Classes for BIM/GIS Integration - Zhu, Junxiang; Wu, Peng (MDPI AG, 2021)
Previous geo-referencing approaches for building information modeling (BIM) models can be problematic due to: (a) the different interpretations of the term ‘geo-referencing’, (b) the insufficient consideration of the placement hierarchy of the industry foundation classes (IFCs), and (c) the misunderstanding that a common way to embed spatial reference information for IFC is absent. Therefore, the objective of this study is to (1) clarify the meaning of geo-referencing in the context of BIM/GIS data integration, and (2) develop a common geo-referencing approach for IFC. To achieve the goal, a systematic and thorough investigation into the IFC standard was conducted to assess the geo-referencing capability of IFC. Based on the investigation, a geo-referencing approach was established using IFC entities that are common in different IFC versions, which makes the proposed approach common to IFC. Such a geo-referencing approach supports automatic geo-referencing that would facilitate the use of BIM models in GIS, e.g., for the construction of digital twins.